PENENTUAN LETAK OPTIMUM ARRESTER PADA GARDU INDUK (GI) 150 kV SIANTAN MENGGUNAKAN METODE OPTIMASI - Ringga Nurhaidi . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2016)
Substation 150 kV Siantan frequent disturbances from lightning strikes. Where based on the results of the analysis in 2015, the number of lightning strikes in the transmission network is approximately 30 times strike. Therefore, we need a protection device to protect this transmission network. The main protection against lightning strikes on the network transmission is lightning arresters. Where, to selecting a reliable arrester for use, note the value of the identifier / rating of the arrester is appropriate for use on a 150 kV substation Siantan. From this research, the results of the analysis and calculation of the value for the distance Optimum arrester on the transformator (S) at 150 kV substations Siantan using lagrange method is 34,784 meter, while the identifier / rating of the arrester to be used are as follows: identifier arester voltage (UC) = 134.64 kV, the working voltage arrester (Ea) = 414.333 kV, operating current arrester (He) = 5.504 kA, Keywords: lightning arrester (LA), lagrange method, the parent Siantan 150 kV Substation